Penyuluhan peningkatan ekonomi masyarakat melalui pengembangan potensi desa wisata di Desa Petalongan Kabupaten Indragiri Hulu - Yasir Yasir; Muhammad Firdaus; Rusmadi Awza; Ismandianto Ismandianto (Unri Conference Series: Community Engagement, 2020)
Petalongan Village is one of the villages in Pasir Penyu District, Indragiri Hulu Regency, which is still left behind. This village has rivers, lakes, and cultural traditions for economic or tourism development. People still do not realize the importance of managing this ecosystem. Therefore, the purpose of this service activity is to change people's behavior in managing and utilizing nature, traditions and culture to improve the community's economy. The targets of this activity are the managers of Village-Owned Enterprises and Women Empowerment of Family Welfare. The service methods carried out started from the socio-economic mapping, counseling, FGD, and mentoring. This community service activity has mapped the economic potential of the village on a lake-based basis. Counseling and FGDs regarding problems in Petalongan Village have contributed to increasing public awareness. Extension activities focused on using the lake for the cultivation of catfish and tilapia. Besides that, training on tourism awareness and UMKM needs to be carried out immediately in order to increase understanding, attitudes and the ability of the community in utilizing the wealth of natural resources in this village. This counseling has a positive impact so that people want to immediately cultivate fish and use the lake for tourism to increase the community’s economic income.